Developing a Community-Based Arabic Language Training Program for Social Empowerment and Sustainable Education in Remote Areas - jumriyah, jumriyah (Journal Ligundi of Community Service, 2025)
Background Remote and underserved communities often face systemic educational exclusion, particularly in accessing quality Arabic language education as a tool for cultural preservation, spiritual development, and social empowerment. The absence of locally relevant, participatory, and sustainable learning models contributes to persistent literacy gaps, weakened communal identity, and diminished access to broader social opportunities. Existing language programs frequently fail to account for local socio-cultural contexts and the need for sustainable community participation. Purpose This study aimed to design a community-based Arabic language training program that promotes social empowerment and sustainable education in remote areas. It integrates socio-linguistic perspectives, participatory education principles, and sustainable development goals (SDGs), particularly SDG 4 (Quality Education) and SDG 10 (Reduced Inequality). The research intends to bridge educational access with cultural relevance and community ownership. Method The study employed a qualitative participatory action research (PAR) methodology. Data were collected through focus group discussions (FGDs), in-depth interviews with local educators and community leaders, and direct observation in selected remote villages. The intervention design was collaboratively constructed with community stakeholders, emphasizing culturally responsive pedagogy, peer-teaching models, and local curriculum integration. Thematic analysis was applied to identify patterns and synthesize community needs and aspirations. Results The findings highlight the centrality of contextualized language materials, community-owned teaching mechanisms, and flexible learning environments. Participants reported increased motivation, identity affirmation, and educational confidence. The program also fostered intergenerational learning, enhanced the role of local mosques and schools, and introduced sustainable practices in educational resource management. The model demonstrated potential scalability with minimal external dependency. Conclusion This study offers a replicable framework for developing Arabic language education programs that are community-driven, culturally embedded, and sustainably managed. It underscores the importance of aligning educational strategies with local values and participatory governance. The model can serve as a reference for policymakers, NGOs, and educational institutions seeking to strengthen educational equity in linguistically and geographically marginalized regions.